19453
|
1 |
(* Title: HOL/Matrix/LP.thy
|
|
2 |
ID: $Id$
|
|
3 |
Author: Steven Obua
|
|
4 |
*)
|
|
5 |
|
|
6 |
theory LP
|
|
7 |
imports Main
|
|
8 |
begin
|
|
9 |
|
|
10 |
lemma linprog_dual_estimate:
|
|
11 |
assumes
|
|
12 |
"A * x \<le> (b::'a::lordered_ring)"
|
|
13 |
"0 \<le> y"
|
|
14 |
"abs (A - A') \<le> \<delta>A"
|
|
15 |
"b \<le> b'"
|
|
16 |
"abs (c - c') \<le> \<delta>c"
|
|
17 |
"abs x \<le> r"
|
|
18 |
shows
|
|
19 |
"c * x \<le> y * b' + (y * \<delta>A + abs (y * A' - c') + \<delta>c) * r"
|
|
20 |
proof -
|
|
21 |
from prems have 1: "y * b <= y * b'" by (simp add: mult_left_mono)
|
|
22 |
from prems have 2: "y * (A * x) <= y * b" by (simp add: mult_left_mono)
|
29667
|
23 |
have 3: "y * (A * x) = c * x + (y * (A - A') + (y * A' - c') + (c'-c)) * x" by (simp add: algebra_simps)
|
19453
|
24 |
from 1 2 3 have 4: "c * x + (y * (A - A') + (y * A' - c') + (c'-c)) * x <= y * b'" by simp
|
|
25 |
have 5: "c * x <= y * b' + abs((y * (A - A') + (y * A' - c') + (c'-c)) * x)"
|
|
26 |
by (simp only: 4 estimate_by_abs)
|
|
27 |
have 6: "abs((y * (A - A') + (y * A' - c') + (c'-c)) * x) <= abs (y * (A - A') + (y * A' - c') + (c'-c)) * abs x"
|
|
28 |
by (simp add: abs_le_mult)
|
|
29 |
have 7: "(abs (y * (A - A') + (y * A' - c') + (c'-c))) * abs x <= (abs (y * (A-A') + (y*A'-c')) + abs(c'-c)) * abs x"
|
|
30 |
by(rule abs_triangle_ineq [THEN mult_right_mono]) simp
|
|
31 |
have 8: " (abs (y * (A-A') + (y*A'-c')) + abs(c'-c)) * abs x <= (abs (y * (A-A')) + abs (y*A'-c') + abs(c'-c)) * abs x"
|
|
32 |
by (simp add: abs_triangle_ineq mult_right_mono)
|
|
33 |
have 9: "(abs (y * (A-A')) + abs (y*A'-c') + abs(c'-c)) * abs x <= (abs y * abs (A-A') + abs (y*A'-c') + abs (c'-c)) * abs x"
|
|
34 |
by (simp add: abs_le_mult mult_right_mono)
|
29667
|
35 |
have 10: "c'-c = -(c-c')" by (simp add: algebra_simps)
|
19453
|
36 |
have 11: "abs (c'-c) = abs (c-c')"
|
|
37 |
by (subst 10, subst abs_minus_cancel, simp)
|
|
38 |
have 12: "(abs y * abs (A-A') + abs (y*A'-c') + abs (c'-c)) * abs x <= (abs y * abs (A-A') + abs (y*A'-c') + \<delta>c) * abs x"
|
|
39 |
by (simp add: 11 prems mult_right_mono)
|
|
40 |
have 13: "(abs y * abs (A-A') + abs (y*A'-c') + \<delta>c) * abs x <= (abs y * \<delta>A + abs (y*A'-c') + \<delta>c) * abs x"
|
|
41 |
by (simp add: prems mult_right_mono mult_left_mono)
|
|
42 |
have r: "(abs y * \<delta>A + abs (y*A'-c') + \<delta>c) * abs x <= (abs y * \<delta>A + abs (y*A'-c') + \<delta>c) * r"
|
|
43 |
apply (rule mult_left_mono)
|
|
44 |
apply (simp add: prems)
|
|
45 |
apply (rule_tac add_mono[of "0::'a" _ "0", simplified])+
|
|
46 |
apply (rule mult_left_mono[of "0" "\<delta>A", simplified])
|
|
47 |
apply (simp_all)
|
|
48 |
apply (rule order_trans[where y="abs (A-A')"], simp_all add: prems)
|
|
49 |
apply (rule order_trans[where y="abs (c-c')"], simp_all add: prems)
|
|
50 |
done
|
|
51 |
from 6 7 8 9 12 13 r have 14:" abs((y * (A - A') + (y * A' - c') + (c'-c)) * x) <=(abs y * \<delta>A + abs (y*A'-c') + \<delta>c) * r"
|
|
52 |
by (simp)
|
|
53 |
show ?thesis
|
|
54 |
apply (rule_tac le_add_right_mono[of _ _ "abs((y * (A - A') + (y * A' - c') + (c'-c)) * x)"])
|
|
55 |
apply (simp_all only: 5 14[simplified abs_of_nonneg[of y, simplified prems]])
|
|
56 |
done
|
|
57 |
qed
|
|
58 |
|
|
59 |
lemma le_ge_imp_abs_diff_1:
|
|
60 |
assumes
|
|
61 |
"A1 <= (A::'a::lordered_ring)"
|
|
62 |
"A <= A2"
|
|
63 |
shows "abs (A-A1) <= A2-A1"
|
|
64 |
proof -
|
|
65 |
have "0 <= A - A1"
|
|
66 |
proof -
|
|
67 |
have 1: "A - A1 = A + (- A1)" by simp
|
|
68 |
show ?thesis by (simp only: 1 add_right_mono[of A1 A "-A1", simplified, simplified prems])
|
|
69 |
qed
|
|
70 |
then have "abs (A-A1) = A-A1" by (rule abs_of_nonneg)
|
|
71 |
with prems show "abs (A-A1) <= (A2-A1)" by simp
|
|
72 |
qed
|
|
73 |
|
|
74 |
lemma mult_le_prts:
|
|
75 |
assumes
|
|
76 |
"a1 <= (a::'a::lordered_ring)"
|
|
77 |
"a <= a2"
|
|
78 |
"b1 <= b"
|
|
79 |
"b <= b2"
|
|
80 |
shows
|
|
81 |
"a * b <= pprt a2 * pprt b2 + pprt a1 * nprt b2 + nprt a2 * pprt b1 + nprt a1 * nprt b1"
|
|
82 |
proof -
|
|
83 |
have "a * b = (pprt a + nprt a) * (pprt b + nprt b)"
|
|
84 |
apply (subst prts[symmetric])+
|
|
85 |
apply simp
|
|
86 |
done
|
|
87 |
then have "a * b = pprt a * pprt b + pprt a * nprt b + nprt a * pprt b + nprt a * nprt b"
|
29667
|
88 |
by (simp add: algebra_simps)
|
19453
|
89 |
moreover have "pprt a * pprt b <= pprt a2 * pprt b2"
|
|
90 |
by (simp_all add: prems mult_mono)
|
|
91 |
moreover have "pprt a * nprt b <= pprt a1 * nprt b2"
|
|
92 |
proof -
|
|
93 |
have "pprt a * nprt b <= pprt a * nprt b2"
|
|
94 |
by (simp add: mult_left_mono prems)
|
|
95 |
moreover have "pprt a * nprt b2 <= pprt a1 * nprt b2"
|
|
96 |
by (simp add: mult_right_mono_neg prems)
|
|
97 |
ultimately show ?thesis
|
|
98 |
by simp
|
|
99 |
qed
|
|
100 |
moreover have "nprt a * pprt b <= nprt a2 * pprt b1"
|
|
101 |
proof -
|
|
102 |
have "nprt a * pprt b <= nprt a2 * pprt b"
|
|
103 |
by (simp add: mult_right_mono prems)
|
|
104 |
moreover have "nprt a2 * pprt b <= nprt a2 * pprt b1"
|
|
105 |
by (simp add: mult_left_mono_neg prems)
|
|
106 |
ultimately show ?thesis
|
|
107 |
by simp
|
|
108 |
qed
|
|
109 |
moreover have "nprt a * nprt b <= nprt a1 * nprt b1"
|
|
110 |
proof -
|
|
111 |
have "nprt a * nprt b <= nprt a * nprt b1"
|
|
112 |
by (simp add: mult_left_mono_neg prems)
|
|
113 |
moreover have "nprt a * nprt b1 <= nprt a1 * nprt b1"
|
|
114 |
by (simp add: mult_right_mono_neg prems)
|
|
115 |
ultimately show ?thesis
|
|
116 |
by simp
|
|
117 |
qed
|
|
118 |
ultimately show ?thesis
|
|
119 |
by - (rule add_mono | simp)+
|
|
120 |
qed
|
|
121 |
|
|
122 |
lemma mult_le_dual_prts:
|
|
123 |
assumes
|
|
124 |
"A * x \<le> (b::'a::lordered_ring)"
|
|
125 |
"0 \<le> y"
|
|
126 |
"A1 \<le> A"
|
|
127 |
"A \<le> A2"
|
|
128 |
"c1 \<le> c"
|
|
129 |
"c \<le> c2"
|
|
130 |
"r1 \<le> x"
|
|
131 |
"x \<le> r2"
|
|
132 |
shows
|
|
133 |
"c * x \<le> y * b + (let s1 = c1 - y * A2; s2 = c2 - y * A1 in pprt s2 * pprt r2 + pprt s1 * nprt r2 + nprt s2 * pprt r1 + nprt s1 * nprt r1)"
|
|
134 |
(is "_ <= _ + ?C")
|
|
135 |
proof -
|
|
136 |
from prems have "y * (A * x) <= y * b" by (simp add: mult_left_mono)
|
29667
|
137 |
moreover have "y * (A * x) = c * x + (y * A - c) * x" by (simp add: algebra_simps)
|
19453
|
138 |
ultimately have "c * x + (y * A - c) * x <= y * b" by simp
|
|
139 |
then have "c * x <= y * b - (y * A - c) * x" by (simp add: le_diff_eq)
|
29667
|
140 |
then have cx: "c * x <= y * b + (c - y * A) * x" by (simp add: algebra_simps)
|
19453
|
141 |
have s2: "c - y * A <= c2 - y * A1"
|
|
142 |
by (simp add: diff_def prems add_mono mult_left_mono)
|
|
143 |
have s1: "c1 - y * A2 <= c - y * A"
|
|
144 |
by (simp add: diff_def prems add_mono mult_left_mono)
|
|
145 |
have prts: "(c - y * A) * x <= ?C"
|
|
146 |
apply (simp add: Let_def)
|
|
147 |
apply (rule mult_le_prts)
|
|
148 |
apply (simp_all add: prems s1 s2)
|
|
149 |
done
|
|
150 |
then have "y * b + (c - y * A) * x <= y * b + ?C"
|
|
151 |
by simp
|
|
152 |
with cx show ?thesis
|
|
153 |
by(simp only:)
|
|
154 |
qed
|
|
155 |
|
|
156 |
end |